2016
DOI: 10.1016/j.amsu.2015.12.048
|View full text |Cite
|
Sign up to set email alerts
|

A cause of severe thigh injury: Battery explosion

Abstract: IntroductionIn parallel with technological improvements, humankind encounter with equipments/devices transforming chemical energy to electrical energy. Especially automobile batteries, watch and mobile phone batteries are the most encountered ones. In the literature, there are mainly facial burn cases due to mobile phone battery explosion. On the other hand very few examples of serious lower limb. injury is present.Presentation of case12-year-old female patient referred to emergency room with skin and soft tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This series also included a 13-year-old boy who suffered an accidental penetrating ocular injury caused by a mobile phone; the responding ophthalmologist stated that the child had “accidentally stabbed himself in the eye while answering the phone”. While the use of mobile phones has previously been implicated in a range of musculoskeletal 34 , 35 and dermatological injuries (through exploding batteries), 36 , 37 to our knowledge, this is the first example of serious ocular trauma due to mobile phone use.…”
Section: Discussionmentioning
confidence: 89%
“…This series also included a 13-year-old boy who suffered an accidental penetrating ocular injury caused by a mobile phone; the responding ophthalmologist stated that the child had “accidentally stabbed himself in the eye while answering the phone”. While the use of mobile phones has previously been implicated in a range of musculoskeletal 34 , 35 and dermatological injuries (through exploding batteries), 36 , 37 to our knowledge, this is the first example of serious ocular trauma due to mobile phone use.…”
Section: Discussionmentioning
confidence: 89%
“…For example, the incidences of taking selfies and sharing them on social media as well as selfie-related behaviors are increasing, particularly among young people, which possibly leads to selfie-related trauma [ 94 , 95 ]. Other studies [ 96 , 97 , 98 ] have reported physical harm caused by mobile phones, such as ear trauma, thigh injuries, electrical burns, and injuries caused by phone explosions. Furthermore, it has been suggested that electromagnetic fields generated by mobile phone may have long-term harmful effects, including an increase in infertility, Alzheimer disease, and other neurodegenerative diseases [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, we have noticed an increase in hospital admissions due to injuries caused by lithium-powered batteries, paralleling the surge in availability of these devices. [9][10][11]15,16 It is acknowledged that lithium batteries containing highly reactive chemicals have the capacity to spontaneously ignite and result in an explosion because of a phenomenon called thermal runaway (when the temperature rises rapidly and the energy stored in the battery is suddenly released). 17 As with any device that has the capacity to store energy, there is an inherent risk for combustion and ignition.…”
Section: Discussionmentioning
confidence: 99%